Deltamethrin Toxicity in a Labrador Dog: A Case Report - Parmar, J. J.; Parikh, P. V.; Amin, N.R.; Dabhi, P.B.; Mahla, J.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
Deltamethrin is a Type-II synthetic pyrethroid widely used in household, agricultural insects and pest  management programmes and in preventing the spread of diseases carried by tick-infested prairie  dogs, rodents and other burrowing animals (Poonam et al., 2013). Deltamethrin has very broad  spectrum control and consider as a most powerful pesticide and has less toxicity among synthetic  pyrethroids in human and mammals (Rehman et al., 2014) and its toxicity has not been reported  in India. This case report describes acute deltamethrin toxicity in a dog.